2020
DOI: 10.1038/s41523-020-00203-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting breast cancer response to neoadjuvant treatment using multi-feature MRI: results from the I-SPY 2 TRIAL

Abstract: Dynamic contrast-enhanced (DCE) MRI provides both morphological and functional information regarding breast tumor response to neoadjuvant chemotherapy (NAC). The purpose of this retrospective study is to test if prediction models combining multiple MRI features outperform models with single features. Four features were quantitatively calculated in each MRI exam: functional tumor volume, longest diameter, sphericity, and contralateral background parenchymal enhancement. Logistic regression analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…We have previously established subtype specific FTV-based prediction models trained using MRI data from 990 I-SPY 2 patients 12 . In this study, multivariable logistic regression analysis was performed to assess the additive value of ctDNA to pCR prediction models based on FTV alone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously established subtype specific FTV-based prediction models trained using MRI data from 990 I-SPY 2 patients 12 . In this study, multivariable logistic regression analysis was performed to assess the additive value of ctDNA to pCR prediction models based on FTV alone.…”
Section: Methodsmentioning
confidence: 99%
“…Clinicopathologic and response data have also been deposited in NCBI's Gene Expression Omnibus and are accessible through GEO SuperSeries accession number https://identifiers.org/geo:GSE150576 39 .The full MRI data will be deposited in The Cancer Imaging Archive (TCIA) and the accession ID is anticipated to be released in mid-2021. When the MRI data become available, the metadata record associated with the group's previous article (https://doi.org/10.6084/m9.figshare.12912191) 40 will be updated to include the TCIA data DOI. Prior to release, MRI data queries can be directed to the corresponding authors (W.L.…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of magnetic resonance imaging (MRI) to discriminate responders from nonresponders has been an active area of research, and one of the goals of trials such as I-SPY and I-SPY2. 1,2 In recent years, "fast"-or "ultrafast"dynamic contrast-enhanced MRI (DCE-MRI) has been introduced for breast imaging, where conventional high-spatial/ low-temporal resolution sequences are substituted for hightemporal resolution imaging, especially during the initial phase of contrast media wash-in. [3][4][5] The use of these sequences has shown that parameters descriptive of initial tumor kinetics can be useful in the diagnosis and characterization of breast lesions.…”
mentioning
confidence: 99%
“…Identifying breast cancer patients who are unlikely to achieve a pathologically complete response (pCR) from neoadjuvant systemic therapy (NAST) early in their treatment could spare nonresponders toxicity from ineffective therapies and direct them toward alternative treatments that could result in better outcomes. The use of magnetic resonance imaging (MRI) to discriminate responders from nonresponders has been an active area of research, and one of the goals of trials such as I‐SPY and I‐SPY2 1,2 . In recent years, “fast”—or “ultrafast”—dynamic contrast‐enhanced MRI (DCE‐MRI) has been introduced for breast imaging, where conventional high‐spatial/low‐temporal resolution sequences are substituted for high‐temporal resolution imaging, especially during the initial phase of contrast media wash‐in 3–5 .…”
mentioning
confidence: 99%